Drought-resistance of Diospyros L. species introduced in the Ukrainian Forest-Steppe (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Drought-resistance of persimmon species and cultivars in the Ukrainian Forest-Steppe is studied. Morphological features of stomatal apparatus of leaves in relation to drought resistance are determined.
Keywords: Diospyros L., drought-resistance, stomatal apparatus, introduction, the Ukrainian Forest-Steppe.